Constitutional Dualities: Reconciling Islamic Normativity with Common Law Principles in Hybrid Legal Systems - Seema Gul; Riaz Ahmad; Dr. Sami Ur Rahman (Indus Journal of Social Sciences, 2025)
Hybrid legal systems that integrate Islamic law with common law traditions present a unique constitutional challenge marked by normative duality and institutional complexity. This article examines the tension between divine normativity and secular legal rationality in states such as Pakistan, Malaysia, and Nigeria, where constitutions simultaneously endorse Islamic principles and uphold common law frameworks. The purpose of the study is to explore how courts and legislatures negotiate this duality, what implications it has for legal coherence, human rights, and rule of law, and how doctrinal reconciliation might be achieved. Employing a comparative legal analysis, the research draws on constitutional texts, judicial decisions, and theoretical literature to assess how legal pluralism functions in practice. The findings reveal that while interpretive harmonization and jurisdictional compartmentalization offer partial solutions, ambiguity and conflict persist due to inconsistent jurisprudence and weak institutional delineation. The study argues for a principled framework grounded in legal pragmatism and the objectives of Islamic law (maqasid al-Shari‘a) to foster coherence and constitutional integrity. Ultimately, the article contributes to broader debates on constitutionalism in pluralistic societies and offers pathways for reconciling competing legal traditions within a single constitutional order. The coexistence of Islamic legal norms and common law traditions within hybrid constitutional systems presents profound interpretive and institutional challenges. This article explores how such dualities manifest in constitutional governance, examining their implications for legal pluralism, judicial reasoning, and democratic accountability. Focusing on jurisdictions like Pakistan, Nigeria, and Malaysia, it evaluates the strategies through which courts and legislatures negotiate these tensions, proposing pathways toward a more coherent jurisprudential synthesis.